2006
DOI: 10.1892/0891-6640(2006)20[20:tnicca]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Neutrophils in Cats: Clinical and Clinicopathologic Features, and Disease Prevalence and Outcome—a Retrospective Case Control Study

Abstract: Toxic neutrophils exhibit a variety of nuclear and cytoplasmic abnormalities in Romanowsky-stained blood smears, and are associated with inflammation and infection. The purpose of the retrospective study reported here was to investigate the association of toxic neutrophils with clinicopathologic characteristics, diseases, and prognosis in cats. Cats with toxic neutrophils (n = 150) were compared with negative-control cats (n = 150). Statistical analyses included Fisher exact, independent t-, nonparametric Mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 11 publications
2
34
1
1
Order By: Relevance
“…A rapid increase in leucocytes is not, therefore, absolutely specific for inflammation. Segev et al (2006) have shown that only about 50% of cats with subacute or chronic inflammation actually had increased number of neutrophils and the degree of neutrophilia was usually higher when inflammation was localised (e.g. in abscesses, pyometra etc.…”
Section: Leucocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…A rapid increase in leucocytes is not, therefore, absolutely specific for inflammation. Segev et al (2006) have shown that only about 50% of cats with subacute or chronic inflammation actually had increased number of neutrophils and the degree of neutrophilia was usually higher when inflammation was localised (e.g. in abscesses, pyometra etc.…”
Section: Leucocytosismentioning
confidence: 99%
“…Accordingly, a lack of leucocytosis does not necessarily exclude the presence of inflammation. Indeed, the most prevalent finding in cats with inflammation seems to be the presence of toxic neutrophils (Segev et al, 2006).…”
Section: Leucocytosismentioning
confidence: 99%
“…These are defined as a collection of cytoplasmic alterations resulting from accelerated production in the bone marrow, including cytoplasmic basophilia, cytoplasmic vacuolation, D€ ohle bodies, and toxic granulation. 3,7,8 Neutrophil toxic change might be an early indicator of acute systemic illness and has been associated with disease severity, case fatality, hospitalization duration, and cost of treatment in dogs. 7 Similarly, in cats, the detection of toxic neutrophils is associated with disease severity, duration of hospitalization, and treatment cost.…”
mentioning
confidence: 99%
“…7 Similarly, in cats, the detection of toxic neutrophils is associated with disease severity, duration of hospitalization, and treatment cost. 8 To our knowledge, no studies have been conducted that have specifically evaluated band neutrophils and toxic change in adult equine emergency admissions and therefore, the value of the microscopic review of peripheral blood smear in adult horses is unknown. Additionally, the microscopic evaluation of the blood smear is frequently underutilized in private veterinary clinics that have in-house hematology analyzers, potentially leading to loss of clinically valuable information.…”
mentioning
confidence: 99%
“…In one study the presence of toxic neutrophils was associated with longer hospitalization. 102 This same study also found that, unlike dogs, toxicity was not associated with increased mortality in cats. Toxic granules represent severe inflammation and, in Birman cats, must be differentiated from the nonpathologic neutrophil granulation anomaly seen in this breed.…”
Section: Inflammatory Leukogrammentioning
confidence: 99%